2017
DOI: 10.1149/2.0741709jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Smooth and Nanoscale Rough Pt(111): An In Situ Surface X-ray Scattering Study

Abstract: The potential dependent surface structure of Pt(111) electrodes in electrochemical environment was studied by in situ crystal truncation rod measurements and in operando grazing incidence small angle X-ray scattering. Determination of the interface structure in the oxidation region reveal a continuous increase of the coverage of place exchanged atoms toward more positive potentials. The resulting oxide consists of an oxygen rich outer and a Pt-rich inner atomic layer. With increasing potential the oxide approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 45 publications
(74 reference statements)
7
45
0
Order By: Relevance
“…However, their X-ray absorption near edge structure (XANES) measurements on Pt nanoparticles suggested that the PE mechanism commences as soon as 0.75 V. These XANES observations could be due to a different oxidation reactivity associated with the finite size as well as the presence of other crystal facets and step sites on the nanoparticles. Indeed, GISAXS measurements of nanoscale roughened Pt(111) surfaces also provided evidence of the surface oxidation shift to lower potentials, which was attributed to the step edge oxidation [37].…”
Section: Resultsmentioning
confidence: 97%
“…However, their X-ray absorption near edge structure (XANES) measurements on Pt nanoparticles suggested that the PE mechanism commences as soon as 0.75 V. These XANES observations could be due to a different oxidation reactivity associated with the finite size as well as the presence of other crystal facets and step sites on the nanoparticles. Indeed, GISAXS measurements of nanoscale roughened Pt(111) surfaces also provided evidence of the surface oxidation shift to lower potentials, which was attributed to the step edge oxidation [37].…”
Section: Resultsmentioning
confidence: 97%
“…Initially both {100} and {111} steps (more precisely, these step sites should be denoted as < 110 > /{100} and < 110 > /{111} respectively, that is, steps along a direction equivalent to [110] and exhibiting a square {100} or hexagonal {111} geometry) form on the roughened surface, while eventually only {111} steps remain. Advanced in situ EC-STM 16,17 and X-ray reflectivity [18][19][20][21][22] experiments are ideal tools to study this system at the atomic level. Using X-ray scattering experiments, and following the surface evolution for 20 ORCs, Ruge et al observed an increasing island size with increasing cycle number and decreasing upper potential limit 21 .…”
mentioning
confidence: 99%
“…In contrast, monocrystalline electrodes are the surfaces of choice to study the atomic scale’s structural transformation process ( 18 , 19 ). Studying cathodic corrosion on monocrystalline surfaces allows tracking the changes from a well-defined atomic structure to a corroded (roughened) surface and correlates the surface etch patterns obtained in the polycrystalline and monocrystalline electrode ( 20 23 ). Such an atomistic understanding may ultimately guide approaches to avoid cathodic corrosion or to design procedures to make tailored nanoparticles via cathodic corrosion.…”
mentioning
confidence: 99%